2021
DOI: 10.1093/scan/nsab067
|View full text |Cite
|
Sign up to set email alerts
|

tDCS effect on prosocial behavior: a meta-analytic review

Abstract: Previous studies have shown that transcranial direct current stimulation (tDCS) could potentially promote prosocial behaviors. However, results from randomized controlled trials (RCTs) are inconsistent. The current meta-analysis aimed to assess the effects of anodal and cathode tDCS using single session protocols on prosocial behaviors in healthy young adults, and explore potential moderators of these effects. The results showed that compared with sham stimulation, anodal (excitatory) stimulation significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Neurostimulation studies implicating dlPFC in social decision making have shown seemingly divergent results with both excitation and inhibition of this region increasing prosociality (Yuan et al, 2022). Gross et al (2018) attempted to explain these discrepant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Neurostimulation studies implicating dlPFC in social decision making have shown seemingly divergent results with both excitation and inhibition of this region increasing prosociality (Yuan et al, 2022). Gross et al (2018) attempted to explain these discrepant findings.…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed to understand the relationship between parental psychological control and prosocial behavior in children and adolescents. Understanding the influences of parenting styles on child development is a critical task of developmental psychology [ 56 ], and prosocial behavior is a vital component of developmental goals with a composite and multidimensional construct [ 57 ]. Due to this importance and omnipresence, prosocial behavior has received considerable attention around the world [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parental control has been found to have an important effect on self-efficacy in many studies [ 70 , 71 ]. A good family environment gives children more attention and support, which results in higher self-efficacy [ 57 , 72 ]. Meanwhile, various studies suggest that self-efficacy is determinant of prosocial behavior [ 22 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Cognitive control and the DLPFC play prominent roles in complying with social norms, including those related to fairness. 34,35 The causal association of DLPFC function with prosocial behaviour has been demonstrated as decreased and increased prosocial decisions through cathodal (inhibitory) and anodal (excitatory) transcranial direct current stimulation (tDCS), respectively, over the DLPFC. 34 Considering that physical activity has been shown to be associated with greater cognitive control and DLPFC function, [15][16][17] it is plausible to hypothesise that physical activity is positively associated with prosocial behaviour.…”
mentioning
confidence: 99%
“…34,35 The causal association of DLPFC function with prosocial behaviour has been demonstrated as decreased and increased prosocial decisions through cathodal (inhibitory) and anodal (excitatory) transcranial direct current stimulation (tDCS), respectively, over the DLPFC. 34 Considering that physical activity has been shown to be associated with greater cognitive control and DLPFC function, [15][16][17] it is plausible to hypothesise that physical activity is positively associated with prosocial behaviour. The second LPFC system of interest in this study was inter-brain synchrony, which involves neural oscillations within specific frequency bands that synchronise across the brains of individuals engaged in social interactions.…”
mentioning
confidence: 99%